Interfascicular Resection of Benign Peripheral Nerve Sheath Tumors. Issue 2 (April 2019) - Stone, Jonathan J.; Puffer, Ross C.; Spinner, Robert J.
Abstract : Background: Interfascicular resection is a surgical technique used to safely treat benign peripheral nerve sheath tumors through careful dissection of functional neural elements off the tumor surface1, 2 . Description: Proper operative technique is essential to improving symptoms, preserving neurologic function, and minimizing the chance for recurrence. Accurate tumor localization, ideal patient positioning, and placement of a longitudinal incision permit adequate exposure. Prior to tumor resection, normal nerve should be identified proximally and distally and controlled with vessel loops. This allows functional fascicles streaming around the tumor in the pseudocapsule to be visualized during resection. A fascicle-free window is identified on the tumor surface through visual inspection and intraoperative neurophysiology monitoring if desired. The pseudocapsule layers are divided with a sharp instrument until a smooth and shiny true capsule layer is found. This plane should have minimal resistance and is developed circumferentially until the tumor can be enucleated in toto. At the poles of the tumor, a single nonfunctional nerve fascicle that courses into the tumor is typically found. If there is >1 fascicle running into the tumor, further pseudocapsule layers should be undermined to sweep fascicles off the true capsule surface. The entering-exiting fascicle can be tested for function and is cut sharply. The specimen should be sent to pathology for permanent sectioning. The sides of the pseudocapsule are spread in opposite directions to evaluate for residual tumor, and any remaining tumor is removed if it can be done safely. Meticulous hemostasis is achieved, and the surgical site is closed in anatomical layers. Alternatives: Pain is the most common presenting symptom, and neuroleptic medications should be used in escalating dosage prior to surgical intervention. Nonoperative medical therapy does not typically result in symptom freedom, and patients often opt for resection. For tumors that are suspected of being malignant, an image-guided percutaneous or open biopsy and staging (positron emission tomography and/or computed tomography scans of the chest, abdomen, and pelvis) are recommended prior to treatment planning. For symptomatic benign extremity lesions, surgical resection is the treatment of choice, and adjuvant therapies like radiation and/or chemotherapy are not recommended. For malignant lesions, more aggressive surgery (wide resection or amputation) and preoperative, intraoperative, or postoperative radiation with or without chemotherapy are often utilized. Rationale: The treatment approach depends on a variety of presenting features such as onset, progression, symptom severity, tumor size, location, imaging features, presence of a syndrome, and patient age. There is little benefit from the resection of an incidentally found, small, nongrowing lesion. The most common reasons for removal of extremity lesions are a painful mass and/or radiating "nerve" pain. There is a high likelihood of relieving the symptoms and minimizing the risk of recurrence, and a relatively low risk of causing neurologic injury. The procedure provides a definitive diagnosis. For patients with severe pain, progressive weakness, rapid tumor growth, or concerning imaging characteristics, biopsy should be considered to determine malignant potential.